Strategi Pencegahan Kejahatan Direktorat Reserse Kriminal Khusus (DIRKRIMSUS) Polda Riau Dalam Pemberantasan Kasus Tindak Pidana Perdagangan Barang Impor Ilegal di Provinsi Riau - Willy Darmansyah; Rio Tutrianto (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2025)
Trading activities of illegal imported goods entering the territory of the Republic of Indonesia are increasingly occurring. Even though the Government itself has established various legal products to protect the implementation of import activities to meet the needs of the people. These illegal products can include children's toys, ceramics, used clothes, used electronics, foreign cigarettes that do not have Indonesian excise stamps attached to them, liquor (drinks containing ethyl alcohol) and other products. This is done to gain large profits. These conditions ultimately make trade in Indonesia increasingly necessary to be monitored. Using qualitative methods to conduct in-depth interviews with several selected sources. This research explains that the forms included in the first phase, namely primary crime prevention strategies, are carrying out routine patrols and raids, as well as using technology when working under intensive supervision. Included in this is public education in increasing awareness and participation with the community to protect their territory. The situation that is classified in the second phase, namely the secondary crime prevention strategy as an effort by the Ditreskrimsus in eradicating criminal cases of trafficking in illegally imported goods in Riau Province, is to carry out a strict law enforcement process. Next, confiscate and destroy illegal goods. In the third phase, namely the tertiary crime prevention strategy, the category of action reflected in this is collaboration between agencies and analysis of smuggling cases that have occurred.